Association between tracking of extracurricular sports practice and weight status during childhood: a prospective cohort study - Weber, Vinícius Müller Reis; Costa, Julio Cesar da; Gonçalves, Hélcio Rossi; Machado, Vitor Hugo Ramos; Romanzini, Marcelo; Ronque, Enio Ricardo Vaz (São Paulo Medical Journal, 2021)
BACKGROUND: Overweight and obesity have reached epidemic prevalences. Obesity control involves many factors and needs to begin early in childhood. OBJECTIVES: To ascertain the association between tracked extracurricular sports practice and weight status; and to analyze tracking of overweight and obesity among school-aged children. DESIGN AND SETTING: Prospective cohort study conducted in 13 public schools in Cianorte, Paraná, in 2012-2016. METHODS: The sample comprised 2459 schoolchildren in Cianorte, of mean age 6.3 years at baseline and 9.4 years at follow-up. Body mass index was calculated from body mass and height measurements. The children were grouped as normal weight, overweight or obese. Information on extracurricular sports practice was collected through the dichotomous question “Do you participate in any extracurricular sports?” (“yes” or “no”).RESULTS: Tracking of weight status showed that 75.5% maintained this, with kappa of 0.530. Tracking of extracurricular sports practice showed that 80.9% maintained this, with low concordance (kappa of 0.054). Weight status correlation between baseline and follow-up showed that overweight or obese individuals were 4.65 times (CI: 4.05-5.34) more likely to maintain the same classification or move from overweight to obese at follow-up. Correlation of extracurricular sports practice with overweight or obesity at follow-up was not significant. CONCLUSIONS: These results demonstrated that overweight or obese children were at higher risk of gaining weight than were normal-weight children. In addition, the proportion of these children who maintained extracurricular sports practices over the years was low. Maintenance of this variable was not associated with weight status.